Conquistadors and Aztecs a history of the fall of Tenochtitlan - Rinke, Stefan 1965- (Oxford University Press, 2023)
Here is a highly readable narrative of the causes, course, and consequences of the Spanish Conquest, incorporating the perspectives of many Native groups, Black slaves, and the conquistadors, timed with the 500th anniversary of the fall of the Aztec capital of Tenochtitlan
Keywords: Cortés, Hernán / 1485-1547; Geschichte; History / ukslc; History of the Americas / thema; Tenochtitlàn, Battle of, Mexico City, Mexico, 1521; Aztecs / History; Eroberung Mexikos; Azteken; Mexico / History / Conquest, 1519-1540